Renewable energy sources operational performance evaluation with hybrid model - Pandey R.K.; Kumar H. (My University, 2025)
Different renewable energy sources can complement each other, multi-source hybrid renewable energy systems have great potential to provide higher quality and more reliable power to customers than a system based on a single resource. This paper provides a method for calculating potential of wind energy and solar energy with proper modeling of wind and solar power. An algorithm along with simulation process has been developed to find the reliability of hybrid system consisting of solar and wind energy using past 2-3 years data of solar radiation, wind speed and load to be served. The simulation process is then used to find the combination of wind and solar energy for which maximum service reliability has been achieved. © 2017 IEEE.